'Vél' d'Hiv' six-day race: the spirit of Paris during the twenties. Issue 1 (2nd January 2017) - Bauer, Thomas; Froissart, Tony
ABSTRACT: The Vélodrome d'Hiver, known colloquially as 'Vél' d'Hiv', was a major sports venue located in Paris, not far from the Eiffel Tower. Used for ice hockey, boxing, wrestling and other events, it was above all the scene of a famous cycling competition: the Six-Day Race. It enjoyed such success that it became a source of artistic inspiration, both in painting, literature and film. La Ronde infernale (Infernal Circle), a feature film released in French cinemas in 1928, for example, shows how writer and director Henri Decoin and producer Luitz-Morat, captured the venue, race and popular fervour to depict, with precision and empathy, a typical scene of Parisian life in the 1920s. However, far from being a mere portrait of a bygone era, this film, in the same way as all subsequent figurative portrayals, helped to immortalise this site and establish it in the collective memory, to such an extent that it became a 'living metaphor' in Paris. In short, by adopting the principles related to the social history of representations, this paper aims to identify the importance of figurative space in general, and cinema in particular, in the historical, memorial and heritage construction of an ancient temple of French sport.